2017
DOI: 10.1115/1.4037631
|View full text |Cite
|
Sign up to set email alerts
|

Direct Digital Subtractive Manufacturing of a Functional Assembly Using Voxel-Based Models

Abstract: Direct digital manufacturing (DDM) is the creation of a physical part directly from a computer-aided design (CAD) model with minimal process planning and is typically applied to additive manufacturing (AM) processes to fabricate complex geometry. AM is preferred for DDM because of its minimal user input requirements; as a result, users can focus on exploiting other advantages of AM, such as the creation of intricate mechanisms that require no assembly after fabrication. Such assembly free mechanisms can be cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…All AM techniques such as direct energy deposition (DED), powder bed fusion (PBF) all make use of CAD designs [17]. 2.2.2 Subtractive manufacturing Lynn et al [19] described voxel-centered CAM systems that enable direct digital subtractive manufacturing of an assembly-free system. Process preparation for subtractive manufacturing (SM) includes voxel-by-voxel elimination of fabric in the same manner as an additive manufacturing process, which comprises layer-by-layer fabric addition.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…All AM techniques such as direct energy deposition (DED), powder bed fusion (PBF) all make use of CAD designs [17]. 2.2.2 Subtractive manufacturing Lynn et al [19] described voxel-centered CAM systems that enable direct digital subtractive manufacturing of an assembly-free system. Process preparation for subtractive manufacturing (SM) includes voxel-by-voxel elimination of fabric in the same manner as an additive manufacturing process, which comprises layer-by-layer fabric addition.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Future research should employ a hybrid structure for efficiency and practicality. This article examines intensity-based registrations through the context of previous works [8,[12][13][14]32,34] demonstrating the practical application of voxel processing in CAM.…”
Section: Overviewmentioning
confidence: 99%
“…Popular methods used the field are voxel intensity-based [7]. Although these representations are memory intensive compared with parametric surfaces, research in voxel-based CAM [8][9][10][11][12][13][14] has shown some advantages over classical approaches in five-axis machining. Specifically, voxels begin to be profitable as part complexity increases and collision avoidance becomes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Forming is a process where a work piece is molded without adding or reducing material [2]. Subtractive manufacturing is a process that involves using tools to remove unwanted material [3]. In additive manufacturing, the process involves adding material to a finished product [4].…”
Section: Introductionmentioning
confidence: 99%